The Other America : White Working Class Perspectives on Race, Identity and Change - Beider, Harris; Chahal, Kusminder (Book collections on Project MUSE., 2020)
Challenging populist views about the white working class in the US, this book showcases what they really think about the defining issues in today's America. As the 2020 presidential elections draw near, this is an invaluable insight into the complex views on 2016 election candidates, race, identity and cross-racial connections.